National Security Dilemmas in the Israeli-Palestinian Conflict - Luangphane, Chanthaboun; Surjaatmadja, Surachman; Banyu Perwita, Anak Agung (CV RIFAINSTITUT, 2024)
This national journal presents a thorough examination of the intricate national security dilemmas entrenched within the enduring Israeli-Palestinian conflict. The conflict, marked by historical grievances and geopolitical complexities, has proven to be a persistent challenge to regional stability. The study employs a comprehensive analytical framework to dissect the multifaceted dimensions of national security that both Israelis and Palestinians contend with. The analysis begins by delving into the historical roots of the conflict, tracing the evolution of national security concerns from the early stages to contemporary challenges. It scrutinizes the geopolitical landscape, focusing on the intricate interplay of regional actors and global dynamics that contribute to the perpetuation of tensions. The study explores the impact of territorial disputes, resource scarcity, and demographic factors on the security calculus of both parties, shedding light on the intricate web of challenges that define the conflict. Moreover, the journal scrutinizes the role of non-state actors and the influence of international interventions on national security dynamics in the region. It examines how global power politics intersect with local dynamics, shaping the security environment for Israelis and Palestinians alike. The study also evaluates the effectiveness of past peace initiatives and identifies potential pathways toward resolution, considering the implications for national security in the long term